Effective Antimalarial Chemoprevention in Childhood Enhances the Quality of CD4+ T Cells and Limits Their Production of Immunoregulatory Interleukin 10. (10th April 2016) - Jagannathan, Prasanna; Bowen, Katherine; Nankya, Felistas; McIntyre, Tara I.; Auma, Ann; Wamala, Samuel; Sikyomu, Esther; Naluwu, Kate; Nalubega, Mayimuna; Boyle, Michelle J.; Farrington, Lila A.; Bigira, Victor; et al.
Abstract: Background. Experimental inoculation of viable Plasmodium falciparum sporozoites administered with chemoprevention targeting blood-stage parasites results in protective immunity. It is unclear whether chemoprevention similarly enhances immunity following natural exposure to malaria. Methods. We assessed P. falciparum –specific T-cell responses among Ugandan children who were randomly assigned to receive monthly dihydroartemisinin-piperaquine (DP; n = 87) or no chemoprevention (n = 90) from 6 to 24 months of age, with pharmacologic assessments for adherence, and then clinically followed for an additional year. Results. During the intervention, monthly DP reduced malaria episodes by 55% overall ( P < .001) and by 97% among children who were highly adherent to DP ( P < .001). In the year after the cessation of chemoprevention, children who were highly adherent to DP had a 55% reduction in malaria incidence as compared to children given no chemoprevention ( P = .004). Children randomly assigned to receive DP had higher frequencies of blood-stage specific CD4 + T cells coproducing interleukin-2 and tumor necrosis factor α ( P = .003), which were associated with protection from subsequent clinical malaria and parasitemia, and fewer blood-stage specific CD4 + T cells coproducing interleukin-10 and interferon γ ( P = .001), which were associated with increased risk of malaria. Conclusions. In this setting, effective antimalarial chemoprevention fostered the development of CD4 + T cells that coproduced interleukin 2 and tumor necrosis factor α and were associated with prospective protection, while limiting CD4 + T-cell production of the immunoregulatory cytokine IL-10.